Efficacy and Safety of Liraglutide Added to Capped Insulin Treatment in Subjects With Type 1 Diabetes: The ADJUNCT TWO Randomized Trial - Ahrén, Bo; Hirsch, Irl B.; Pieber, Thomas R.; Mathieu, Chantal; Gómez-Peralta, Fernando; Hansen, Troels Krarup; Philotheou, Areti; Birch, Sune; Christiansen, Erik; Jensen, Thomas Jon; Buse, John B. (Diabetes care, 2016)
To investigate the efficacy and safety of liraglutide added to capped insulin doses in subjects with type 1 diabetes. A 26-week, placebo-controlled, double-blind, parallel-group trial enrolling 835 subjects randomized 3:1 receiving once-daily subcutaneous liraglutide (1.8, 1.2, and 0.6 mg) or placebo added to an individually capped total daily dose of insulin. Mean baseline glycated hemoglobin (HbA1c) (8.1% [65.0 mmol/mol]) was significantly decreased with liraglutide versus placebo at week 26 (1.8 mg: -0.33% [3.6 mmol/mol]; 1.2 mg: -0.22% [2.4 mmol/mol]; 0.6 mg: -0.23% [2.5 mmol/mol]; placebo: 0.01% [0.1 mmol/mol]). Liraglutide significantly reduced mean body weight (-5.1, -4.0, and -2.5 kg for 1.8, 1.2, and 0.6 mg, respectively) versus placebo (-0.2 kg). Significant reductions in daily insulin dose and increases in quality of life were seen with liraglutide versus placebo. There were higher rates of symptomatic hypoglycemia (21.3 vs. 16.6 events/patient/year; P = 0.03) with liraglutide 1.2 mg vs. placebo and of hyperglycemia with ketosis >1.5 mmol/L with liraglutide 1.8 mg vs. placebo (0.5 vs. 0.1 events/patient/year; P = 0.01). In a broad population of subjects with long-standing type 1 diabetes, liraglutide added to capped insulin reduced HbA1c, body weight, and insulin requirements but with higher rates of hypoglycemia for liraglutide 1.2 mg and hyperglycemia with ketosis for liraglutide 1.8 mg.